Spring Load

Written by Jerry Ratzlaff on . Posted in Fastener

spring compression 10formulas that use Spring load

\(\large{ P =  T \; n_s   }\)   
\(\large{ P = n_s \; \left( l_i - l_f  \right)  }\)   
\(\large{ P =  n_s \; d_s  }\) (spring rate)

Where:

\(\large{ P }\) = spring load when compressed to length

\(\large{ l_f }\) = final length (compressed)

\(\large{ l_i }\) = initial length (free)

\(\large{ T }\) = travel length

\(\large{ d_s }\) = spring displacement

\(\large{ n_s }\) = spring rate

 

Tags: Equations for Spring